(untitled) (Religious dialogue and cooperation, 2024)
Multiple-holistic analysis conducted in the Western Balkans has shown that context(s) in the Western Balkans are overflowed with stereotypes, prejudice, and religious intolerance. These three phenomena were included in extensive multiple-holistic case study by conducting interviews and open-ended surveys among peace activists, journalists, politicians, as well as members of the civil society, in the countries of North Macedonia, Bosnia and Hercegovina, and Kosovo. The research findings draw a picture of a still deeply prejudiced and divided societies. People categorize each other according to their religion and ethnicity. The group they identified themselves with represents the reference for what is good or bad. Stereotypes and prejudice are deeply rooted in and transmitted in early childhood experiences, in most cases as a result of family trauma as a consequence of an earlier conflict. Also, ethnic prejudice are deeply rooted in state systems. Religion in these contexts plays a crucial but subtle role in designing unstable and divided contexts. It keeps to its own communities and values through exclusion of the others instead of using its power for unifying and tolerance purposes. The presence of deeply rooted stereotypes and prejudice create uncertain societies and uncertainty among people. The conflict contexts in the Western Balkans require a serious and sustainable strategy for building relationships among people regardless of their ethnicity and religious affiliation in the long term.